Study of India–Nepal Relations: An Analysis of Contemporary Dimensions: भारत–नेपाल संबंधों का अध्ययन: समकालीन आयामों का विश्लेषण - Nair, Anila; Meena, Than Singh (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
India and Nepal share deeply rooted historical, cultural, and religious ties marked by mutual interconnection. Open borders, socio-cultural exchanges, and shared traditions make these relations unique. Politically, economically, and strategically, the bond has grown stronger over time. Historical contexts such as the Licchavi period, the flow of Buddhist–Hindu culture, and the freedom struggle provided a lasting foundation for India–Nepal partnership. In contemporary times, these relations have become broader and more complex. On one hand, areas like trade, energy cooperation, education, tourism, and cultural exchanges bring new momentum to collaboration. On the other hand, constitutional disagreements, political instability, China’s growing influence, border disputes, and water-sharing issues pose challenges. The study concludes that geographical proximity, cultural-historical partnership, and economic-strategic cooperation form the core of these relations. If dialogue, trust, and mutual understanding are prioritized, India–Nepal ties can not only strengthen bilateral cooperation but also significantly contribute to peace, stability, and development in South Asia. Abstract in Hindi Language: भारत और नेपाल के संबंध ऐतिहासिक, सांस्कृतिक तथा धार्मिक दृष्टि से अत्यंत गहरे और परस्पर जुड़ाव वाले रहे हैं। दोनों देशों के बीच खुली सीमाएँ, सामाजिक–सांस्कृतिक आदान–प्रदान तथा साझा परंपराएँ इन संबंधों को विशिष्ट बनाती हैं। राजनीतिक, आर्थिक और सामरिक दृष्टि से भी यह रिश्ता निरंतर सुदृढ़ हुआ है। इतिहास में लिच्छवी काल, बौद्ध–हिंदू सांस्कृतिक प्रवाह और स्वतंत्रता संग्राम जैसे प्रसंगों ने भारत–नेपाल की साझेदारी को स्थायी आधार प्रदान किया है। समकालीन संदर्भ में इन संबंधों का स्वरूप और अधिक व्यापक तथा जटिल हो गया है। एक ओर व्यापार, ऊर्जा सहयोग, शिक्षा, पर्यटन और सांस्कृतिक आदान–प्रदान जैसे क्षेत्र सहयोग को नई गति देते हैं, वहीं दूसरी ओर संवैधानिक मतभेद, राजनीतिक अस्थिरता, चीन की सक्रियता, सीमा विवाद और जल–वितरण जैसे मुद्दे चुनौतियाँ प्रस्तुत करते हैं। अध्ययन से यह निष्कर्ष प्राप्त होता है कि भौगोलिक निकटता, सांस्कृतिक–ऐतिहासिक साझेदारी और आर्थिक–सामरिक सहयोग इन संबंधों की नींव हैं। यदि संवाद, विश्वास और आपसी समझ को प्राथमिकता दी जाए, तो भारत–नेपाल संबंध न केवल द्विपक्षीय सहयोग को मजबूत करेंगे, बल्कि दक्षिण एशिया की शांति, स्थिरता और विकास में भी महत्वपूर्ण योगदान दे सकते हैं। Keywords: भारत, नेपाल, द्विपक्षीय संबंध, कूटनीति, व्यापार, सांस्कृतिक जुड़ाव, समकालीन।